INSTRUMENTO DESENVOLVIDO PARA AVALIAÇÃO DE DESEMPENHO DE ACESSIBILIDADE - Brandalise, Fernanda Marisa Pasinato; Cappellesso, Vanessa Giaretton; Stein, Kassio Joe; Bonin, Luis Carlos (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Accessibility has always been an important requirement, but not always contemplated in the design of architectural projects and building facilities. With the dissemination of regulations and technical standards, accessibility has reached a wider range. According to NBR 9050 (ABNT, 2015), accessibility can be defined as the possibility of reaching, perceiving and understanding the use of spaces, furniture, urban equipments, buildings, transportation, information and communication, providing security and autonomy for disabled person or person with reduced mobility. The difficulties encountered in analyzing and applying the requirements of NBR 15575 (ABNT, 2013) and NBR 9050 (ABNT, 2015) in the projects and executions incited the development of a proposal for an instrument for assessing accessibility performance through tabulation in spreadsheet. This instrument was developed to assist the application of the evaluation methods by design analysis and visual inspection. In order to verify the usefulness of such a tool, it was applied in the accessibility evaluation of a public school. Among the requirements of the NBR 9050 standard (ABNT, 2015), 52% applied to the object of study. The results show that among the requirements that applied only 25% were considered in the project and 18% were fulfilled in execution.